2007
DOI: 10.1007/s12110-007-9024-y
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Controversy

Abstract: Critics of evolutionary psychology and sociobiology have advanced an adaptationists-as-right-wing-conspirators (ARC) hypothesis, suggesting that adaptationists use their research to support a right-wing political agenda. We report the first quantitative test of the ARC hypothesis based on an online survey of political and scientific attitudes among 168 US psychology Ph.D. students, 31 of whom self-identified as adaptationists and 137 others who identified with another non-adaptationist meta-theory. Results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Evolutionary studies provide a case in point: Scientists who adopt an evolutionary approach are perceived as concealing a conservative agenda (Segestrale, 2000), when in fact evolutionary psychologists (Tybur, Miller & Gangestad, 2007) and anthropologists (Lyle & Smith, 2012) are substantially more liberal than the general public, and no different ideologically from their departmental peers with other research foci. In conjunction with other recent studies, the present work provides a plausible explanation: Evolutionary methodsmuch like behavioral genetics-explain human behavior in terms of intrinsic, biological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Evolutionary studies provide a case in point: Scientists who adopt an evolutionary approach are perceived as concealing a conservative agenda (Segestrale, 2000), when in fact evolutionary psychologists (Tybur, Miller & Gangestad, 2007) and anthropologists (Lyle & Smith, 2012) are substantially more liberal than the general public, and no different ideologically from their departmental peers with other research foci. In conjunction with other recent studies, the present work provides a plausible explanation: Evolutionary methodsmuch like behavioral genetics-explain human behavior in terms of intrinsic, biological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Evolutionary psychologists defend their discipline by asserting that these arguments are based on misunderstandings. Tybur and Miller (2007) "tested the controversy" and found that scholars in EP are actually less conservative than a typical US citizen. EP scholars also argue that the field does take culture and social learning into account, and that both genes and environment are involved in any manifest human behaviour (Confer et al, 2010;Buss & Schmitt, 2011).…”
Section: Evolutionary Psychology and Lgbtq+ Issues: A Qualitative Stumentioning
confidence: 99%
“…Accusations of "biological determinism" have typically been accompanied by claims that belief in genetic causes undermines the hope of altering human behavior in ways concordant with liberal or progressive social ideals. Or more aggressively, that belief in genetic causes provides a biologically grounded sanction for violence and for existing distributions of social power (Sociobiology Study Group 1976;Lewontin 1980;Lewontin, Rose, and Kamin 1984;Degler 1991;Buss and Malamuth 1996;Segerstråle 2000;Pinker 2002;Vandermassen 2005;Tybur, Miller, and Gangestad 2007;Duarte et al 2015). A model of personality that incorporates a conception of "honesty" (the "H Factor") might help integrate hypotheses about underlying qualities of intellectual character with hypotheses of direct causal relationships between belief in science and belief in genetic influences (Chirumbolo and Leone 2010;Lee and Ashton 2012;Rindermann, Flores-Mendoza, and Woodley 2012;de Vries et al 2016).…”
Section: Scientific Explanation and Beliefs About Biology And Culturementioning
confidence: 99%